Effects of DARSI Intervention Program on Adolescents’ Perceptions of Love, Tolerance toward Abuse and Dating Violence Perpetration - María-Jesús Cava; Laura Carrascosa; Sofía Buelga (Adolescents, 2022)
Teen dating violence is a serious problem and intervention programs aimed at reducing this violence and helping adolescents to develop healthier romantic relationships are needed. The objective of this study was to assess the effects of the DARSI program on the development of a more adequate perception of love, the reduction of tolerance toward abuse in romantic relationships, and the reduction of the perpetration of dating violence in adolescents. The sample consisted of 129 adolescents, aged 12 to 17 years (M = 14.05, SD = 1.08). A repeated measures (pre-test and post-test) quasi-experimental design with an intervention group and a control group was used to assess the effects of the program. The results showed significant decreases in unhealthy perceptions of love (linking love with control and dependence), tolerance toward abuse in romantic relationships, and dating violence perpetration in the intervention group. Healthier perceptions of love (linking love with respect and communication) were observed in the intervention group after the implementation of this program. These findings support the implementation in educational contexts of programs focused on the development of non-violent and healthy romantic relationships in adolescents.